A Study of the Barriers to the Implementation of Blended Learning - Sam, Man Keong; Soong, Cai Juan (2016)
There has been fast growing of blended courses (hybrid or mixed-mode courses) where a portion of the traditional face to face instruction is replaced by online learning. Blended courses have claimed as one of the famous choices for students in overseas colleges and universities due to its much advantage of flexibility and convenient compare with face to face classroom experience. However, adopting a new teaching approach is always a daunting and challenge task in an early adopted stage with limited resource circumstances. This paper aims to identify the barriers to the implementation of blended learning. Data is collected using questionnaire survey method. Finding shown that most students were aware of the Blackboard (BB) learning platform.